Plan de negocio para la elaboración de manufacturas de vidrio reciclado, con insumos importados de Colombia - Morales Jaramillo, David Ernesto (2017)
The present business plan analyzes and evaluates the feasibility of installing an artisan plant for the treatment of recycled glass and the elaboration of manufacturing based on it in the city of Quito concentrating in all the small restaurants and establishment of the daily lunches of the zonal administration Eugenio Espejo, Eloy Alfaro and all public markets. The fundamental purpose of the business is the introduction of glassware for domestic use at an affordable price, which are 100% handcrafted and meet the technical requirements and specific characteristics of the industry, from recycled glass with inputs imported from Colombia to Cleaning, hygiene and coloring thereof, the highest degree of strength, quality and precision in order to help the environment and reduce glass waste and the impact it generates. Through an advisory and direct sales with the customer assuring delivery domicile of the product.